EFEKTIVITAS PENGGUNAAN PUPUK ORGANIK KASCING DAN PUPUK ORGANIK CAIR PADA PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculantum Mill) - Nurhaeni Sanda; Netty Syam (Percetakan Umi Toaha Makassar, 2018)
This research aims to 1) get the best effect of organic kascing fertilizer on growth and production of tomato plants. 2) Getting the best concentration of Lestari Green liquid organic fertilizer on growth and production of tomato plants. 3) Obtain a combination of organic kascing fertilizer dosage and concentration of liquid organic fertilizer Lestari Green on growth and production of tomato plants. This research was conducted from January to April 2017 in Sudiang Biringkanaya district., Makassar City, South Sulawesi, design with a two factor randomized block design was observed, the dose of kascing fertilizer consisted of 4 levels: control 0 , 5 tons / ha, 7.5 tons / ha and 10 tons. The liquid organic fertilizer factor consists of 4 levels: Control, 5cc / L water, 10 cc / L water, 15 cc / L water. The results showed that 1) The use of Kascing organic fertilizer with a dose of 10 tons / ha gives the best effect of average height of plants that is 46.04 cm, the fastest flowering age of 31.14 days, productive branches as much as 2.30, the number of fruit tebanyak is 28.28 plant, 1.69 kg of plantation, and fruit / hectare production of 11.11 ton / hectare, 2) The use of Lestari Green liquid organic fertilizer with concentration of 15 cc / L water gives the best influence on the average of good plant height that is 43.01 cm, the fastest flowering age of 31.69 day, productive branch as much as 2.23, fruit weight as much as 1.65 kg of crop, weight of fruit per plot of 6.03 kg and fruit / hectare production of 41.86 tons / hectare, 3) Combination of organic fertilizer treatment of kascing and liquid organic fertilizer Lestari Green which can improve growth and increase the production of tomato plants is the treatment of organic fertilizer kascing 10 tons / hectare and concentration p liquid organic fertilizer Lestari Green 15 cc / L water on parameter Number of leaves and number of fruit.